Characterization of Local Muhfud Avocado from West Bangka as a Germplasm Conservation Strategy in Bangka Belitung - Ningsih, Riski Meliya; Susianti, Helda; Lesta, Lesta; Lise, Alaini; Saputri, Amanda (Jurnal Ilmu Pertanian, 2026)
West Bangka Regency has significant potential from its local avocado accession, Muhfud, which has been cultivated and adapted to local agroecological conditions for decades. However, this accession has not been registered as a variety, rendering it vulnerable to genetic erosion and misappropriation. This study aimed to characterize the morphological traits of Muhfud avocado accession from West Bangka Regency as a step toward preserving local germplasm. Qualitative and quantitative morphological observations were performed on vegetative, generative, and fruit traits. The study was conducted from August to October 2025, employing purposive sampling on five trees, including the original parent tree. Characterization followed the descriptor for avocado, encompassing tree organs, leaves, flowers, fruits, and seeds. The results indicate that Muhfud accession exhibits distinctive morphological features, such as a semi-circular tree architecture, type B flowering, a clavate fruit shape with buttery-smooth, doughy texture, and fruits that are longer with thinner skin compared to other local varieties such as Muntok accession. Variations in mean values and standard deviations of quantitative morphological characters (particularly fruit weight of 358.40 ± 29.04 g, tree height of 5.90 ± 2.32 m, and stem circumference of 70.12 ± 26.67 cm for Muhfud accession) suggest strong genetic potential and adaptation to the local agroecological conditions of West Bangka Regency. These characteristics support the development of locally adapted, productive, and storage-resilient superior varieties. In conclusion, the findings contribute to germplasm conservation efforts and the advancement of local avocado breeding programs in tropical Indonesia.